Design of a composite crash box for a Formula Student team car: preliminary testing and model tuning - Santos, André Miguel Almeida (2018)
In this work, preliminary studies towards the development of a structural carbon fibre nose for a Formula Student team car are presented. Numerical and experimental approaches have been considered to evaluate the impact behaviour of composite tubes. Then, finite element simulations are used to determine the crush stress by fitting the numerical results to the experimental data. The crush stress is also validated using quasi-static compression tests. The obtained results are compared and discussed in the framework of the future structural nose and crashbox design. The obtained results are compared and discussed in the framework of the future structural nose and crashbox design.